Aging, Chronic Kidney Disease, and Psychological Resilience - Ali Zafer; Sawal Baloch (Indus Journal of Bioscience Research, 2023)
Aging is an inevitable biological process that affects every individual, and with it comes an increased risk of various health conditions, including Chronic Kidney Disease (CKD). CKD is a complex and progressive condition that not only poses physical health challenges but also significantly impacts an individual's psychological well-being. In the face of such adversity, the concept of psychological resilience emerges as a critical factor in determining how individuals cope with the challenges associated with aging and CKD. This paper explores the multifaceted relationship between aging, CKD, and psychological resilience. It delves into the physiological and psychological aspects of aging and CKD, examines the prevalence and impact of CKD on the elderly population, and investigates the concept of psychological resilience as a vital coping mechanism for individuals with CKD. Additionally, this paper discusses the various interventions and strategies that can be employed to enhance psychological resilience in the aging CKD population, ultimately aiming to improve their overall quality of life.